Slow-type Interval Training and Ethanol Extract of Sarang Semut (Myrmecodia pendans) can Improve the Early Lesions of Atherosclerosis in Type-2 Diabetes Mellitus Rats - Daulay, Milahayati; Lindarto, Dharma; Sembiring, Rosita Juwita; Machrina, Yetty; Purba, Ambrocius; Munir, Delfitri; Wahyuni, Arlinda Sari; Yamamoto, Zulham (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Macrovascular complications in diabetes mellitus (DM) are the most common cause of death in DM patients. The formation of foam cells on the endothelium is an early marker of atherosclerotic lesions. Physical exercise and antidiabetic agents are an integral part of the management of DM. AIM: The purpose of this study was to analyze the synergistic effect of slow-type interval training (STIT) and ethanol extract of Sarang Semut (EESS) on the number of foam cells in type-2 DM (T2DM) rats. METHODS: A total of 25 male Wistar rats were induced into a type-2 DM model with a high-fat diet and low-dose Streptozotocin injection. Rats were divided into four groups consisting of G1 (T2DM/T2DM), G2 (T2DM + STIT), G3 (T2DM + EESS), and G4 (T2DM + combination of STIT and EESS). The slow-type interval training exercise is done by running on a treadmill. Ethanol extract of Sarang Semut was given at a dose of 400 mg/kg BW for 8 weeks. Histopathological examination was performed with Hematoxylin-Eosin staining to examine the number of foam cells in the aorta. Ethical approval was obtained from the Health Research Ethics Committee, Faculty of Medicine, Universitas Sumatera Utara. RESULTS: The results showed that there were differences in the average number of foam cells in each treatment group. The highest number of foam cells was found in the T2DM group. The average number of foam cells was the least in the group that received a combination of STIT and EESS which was statistically different from the group that received STIT (K2) and the group that received EESS (K3). CONCLUSION: It can be concluded that the combination of slow-type interval training and ethanol extract of Sarang Semut can reduce the number of foam cells in T2DM rats.